Outcome of prenatally diagnosed anterior abdominal wall defects. Issue 3 (1st May 1998) - Boyd, P A; Bhattacharjee, A; Gould, S; Manning, N; Chamberlain, P
Abstract : One hundred consecutive cases of confirmed anterior abdominal wall defect, identified prenatally in the Oxford Prenatal Diagnosis Unit over 11 years, were studied. Fifty nine per cent of cases were suspected omphaloceles and 41% suspected gastroschisis. Fifty four per cent of omphaloceles were accompanied by other defects compared with 5% of those with gastroschisis. Overall, 29% of fetuses with omphalocele had an abnormal karyotype, and of those with another abnormality identified on scan (excluding four cases with no karyotype performed), 54% had an abnormal karyotype. Of the 27 cases with suspected isolated omphalocele, 14 were live born, all of whom have survived. If the 11 whose parents opted for termination of pregnancy are excluded, survival to birth was 88%. Six of the suspected isolated omphaloceles have Beckwith Wiedemann syndrome (BWS). Eight (57%) of the live born babies with omphaloceles had major problems up to the age of 2, but only one (7%) has long term major problems. This child has BWS and is deaf.  Of the 39 cases of suspected isolated gastroschisis, 33 (85%) pregnancies resulted in live birth and one in neonatal death after surgery. Survival rate (excluding terminated pregnancies) was 97%. Gastroschisis was associated with a younger maternal age than omphalocele (p<0.001) and lower birthweight centile (p<0.01).  Fifteen per cent of the gastroschisis babies had major problems up to the age of 2 years and 12% long term developmental problems. Ninety three per cent of the omphalocele babies and 88% of those who had gastroschisis have no long term problems. Over the study period there have been major changes in scanning equipment and expertise. Since 1991 no woman with a suspected isolated lesion has opted for termination of pregnancy.